2013
DOI: 10.1002/dc.22953
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle sampling provides appreciable diagnostic yield in lesions of post kala azar dermal leishmaniasis: Analysis of four cases from North Eastern India

Abstract: Post-kala-azar dermal leishmaniasis (PKDL) is a sequel of visceral leishmaniasis (VL), usually occurring 6 months to 3 years after VL. Spectrum of cutaneous lesions in PKDL can be hypopigmented macules, nodules, plaques, or erythema. It is usually diagnosed clinically, supplemented by ancillary techniques like skin smear examination, histopathology, polymerase chain reaction, and monoclonal antibody test. Literature on the role of cytology in the diagnosis of PKDL is extremely limited. Here we highlight the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The need to perform skin biopsy, which is invasive and requires suturing, causes discomfort and limits the number of people who agree to this invasive procedure for diagnostic purposes. Recently, several studies reported the promising diagnostic efficacy of the less invasive slit skin, microbiopsy, and fine needle biopsy methods [ 24 , 33 , 38 , 39 ]. Further validation is needed before these methods can be used for PKDL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The need to perform skin biopsy, which is invasive and requires suturing, causes discomfort and limits the number of people who agree to this invasive procedure for diagnostic purposes. Recently, several studies reported the promising diagnostic efficacy of the less invasive slit skin, microbiopsy, and fine needle biopsy methods [ 24 , 33 , 38 , 39 ]. Further validation is needed before these methods can be used for PKDL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The skin biopsy procedure is invasive and requires surgical set-up, which limits the ability to collect multiple biopsies without negatively impacting patient participation and use as an active field-based case detection method. Several recent studies have indicated the satisfactory diagnostic efficacies of the less invasive slit skin, microbiopsy, and fine needle biopsy methods [21,41,42]. Further evidence is required, however, before these invasive sample collection procedures can be applied for diagnosis of PKDL.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity of PKDL in the Indian subcontinent is prolonged irrespective of the morphology of lesions. Several histopathology studies have gone through the infected skin lesion tissues having numerous intracellular and extracellular L. donovani bodies [5,9,58,73,[127][128][129]. A retrospective study, with biopsies of 88 skin and 16 mucosal lesions of PKDL patients were studied from 2004 to 2011 in Bihar has shown histo-morphological patterns having follicular plugging, grenz zone, and dermal infiltrates arranged in three modes: diffused infiltrates (46.6%), perivascular and perifollicular infiltrates (27.3%), and superficial perivascular infiltrates (18.1%) [127].…”
Section: Histopathologymentioning
confidence: 99%